Crise estrutural do capital, Maquinofatura e a precarização do trabalho: A Questão Social no Século XXI' - Alves, Giovanni Antonio Pinto [UNESP] (My University, 2013)
We will discuss the new determinations of the degradation of work in the historical conditions of the 21st century. Thus, considering the determinations of the structural value appreciation crisis and the prevalence of machinefacture as a new form of capital production, the degradation of work sets itself not only as wage degradation but also as existential degradation, changing the historical records of the social issue in the 21st century. We will briefly explain the concepts of global capitalism, machinefacture, structural value appreciation crisis, existential degradation, just-in-time way of life, and ideological work.

O objetivo do texto é expor as novas determinações da precarização do trabalho nas condições históricas do século XXI. Deste modo, tendo em vista as determinações da crise estrutural de valorização do valor e a vigência da maquinofatura como nova forma de produção do capital, a precarização do trabalho põe-se não apenas como precarização salarial, mas precarização existencial, alterando os registros históricos da questão social no século XXI. Explicaremos, de modo sucinto, o significado dos conceitos de capitalismo global, maquinofatura, crise estrutural de valorização do valor, precarização existencial, modo de vida just-in-time e trabalho ideológico.
Structural crisis of the capital, machinefacture, and the degradation of work – the social issue in the 21st century
Keywords: Precarização do trabalho; Gestão; Saúde do trabalhador